Библия рядового: семикнижие / П. Любомиров ; [художник Ю. А. Наговицын] - Любомиров Петр Петрович (Удмуртия, 1995)
Экземпляры: (20240427) / Инвентарный номер: 23903 / Цена: 32.000 / Сис.шифр: 84(2=664.1) / Авт.знак: Л 93 / ГРНТИ: 17.82 / ББК: 84(2=664.1)